Dampak Sosial Ekonomi dan Lingkungan Pengolahan Kopi Robusta BUMDes Tugu Sari, Desa Pajahan, Kecamatan Pupuan, Kabupaten Tabanan - I PUTU EDI SWASTAWAN; I MADE SUDARMA; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Socio-economic and Environmental Impacts of the Robusta Coffee Processedby the Tugu Sari Village-Owned Enterprise ‘BUMDes’, Pajahan Village,Pupuan District, Tabanan RegencyThe Tugu Sari Village-Owned Enterprise ‘Badan Usaha Milik Desa (BUMDes)’ is aRobusta coffee processing enterprise run by the village. It was established to support theVillage’s Original Income ‘Pendapatan Asli Daerah (PAD)’, improve the local people’sprosperity, serve the local people, improve the management of the village’s assets, andmaximize and sustain the potential which the village, as the one where Robusta coffee isproduced, has. This current study was intended to identify the impact of the existence ofthe Tugu Sari BUMDes, Pajahan Village, based on the sustainable development system.Three impacts were explored in the current study. They are the social, economic andenvironmental impacts. The social and environmental impacts on the existence of theBUMDes were measured through the local people’s perception, and the economicimpact was measured based on the score obtained using the Keynesian economicimpact. The result of the study shows that the local people’s perception of the socialimpact of the BUMDes was good. The economic impact was that the existence of theBUMDes could contribute to the local people’s economy based on the score obtainedthrough the Keynesian multiplier effect, namely 1.35. The local people’s perception wasnot good environmentally, as the noise produced by the coffee processing machinedisturbed the learning process at Elementary School 2 Pajahan. Therefore, it issuggested that the coffee processing machine should be relocated, so it would notdisturb the learning process at Elementary School 2 Pajahan.